Replacement of fish oil with a high-DHA algal oil in a fishmeal-free diet fed to Florida pompano (Trachinotus carolinus) - Riche, Marty; Barrows, Frederic T.; Nilles, Zachary; Mejri, Sahar; Campbell, Kelly; Wills, Paul S. (Frontiers in Aquaculture, 2023)
A 12-week growth trial was conducted to evaluate complete co-replacement of fish meal (FM) and fish oil (FO) in juvenile Florida pompano Trachinotus carolinus diets. Five open-formula experimental diets were formulated as iso-nitrogenous (~46% crude protein) and iso-lipidic (~15% crude lipid). It is assumed Florida pompano lack the mechanisms for synthesizing sufficient LC-PUFA. In the FM/FO-free diets, to meet the dietary LC-PUFA a commercially available Schizochytrium algal oil was used. Four diets were prepared from a basal mix with Spirulina and poultry by-product meal as the principal protein sources. They differed only in their oil source, fish oil (FO), algal oil (AO), soy oil (SO), or a 50/50 blend of algal oil and soy oil (A/S). The fifth experimental diet (control) was a standard open-formula FM diet. In addition to the experimental diets, two commercial closed-formula diets served as references. Seven diets, each with four replicates were stocked with 20 Florida pompano (~ 4 g). The experimental open-formula diets were tested against the control using Dunnett’s t-test. The different oil sources were tested against each other using orthogonal contrasts. The four experimental diets were each tested against the two reference diets with equivalency tests. All production metrics were lower in SO than the control. No differences were observed between the FO, AO, A/S and the control, or between the three diets. Feed conversion ratio was higher in the SO than the control, and no other differences were found. Protein efficiency ratio was higher in the control than the experimental diets. The contrasts indicated FO, AO, and A/S resulted in a lower feed conversion than the SO. The A/S blend performed as well as AO, suggesting this blending approach would reduce feed costs without loss of performance. There were differences in performance between the two commercial reference feeds, underscoring the importance of using well-defined open-formula diets as a reference or control. To our knowledge this is the first study to demonstrate co-replacement of FM and FO can be achieved in Florida pompano. Development of successful open-formula diets, without FO, will help spur innovation and sustainability of aquaculture production.